Factors affecting the continued use of the mobile flash dryers by farmer co-operatives, Nueva Ecija, Philippines : a thesis submitted in partial fulfilment of the requirements for the degree Master of Applied Science (Agricultural Systems Management), Massey University, Palmerston North, New Zealand - Rodriguez, Amelita C (Massey University, 1999)
Harvest of the Philippines second and larger rice crop occurs during the end of the wet season. For members of the rice industry this wet season harvest poses a problem: grain cannot be dried reliably using traditional sundrying methods. Poor drying results in quality reductions and hence farmers receive lower returns. To address this situation the Philippines Government introduced locally manufactured mechanical dryers. This study was undertaken to examine variables which enhance or limit the continued use of the mobile flash dryers in farmers' co-operatives in Nueva Ecija, the Philippines. Two case studies, each consisting of three farmers' co-operatives were investigated using semi-structured interviews. One case comprised co-operatives that continue to use the dryer while the other comprised those that have stopped using it. Results showed that a combination of factors influenced the adoption decisions of the co-operatives. Economic factors, especially the volume of rice handled by the co-operative appeared to be most important. Furthermore, the way that the dryer fitted with the other postharvest systems in the co-operatives was a determinant of adoption decisions. In particular, the co-operatives with rice milling operations or with inadequate alternative drying options utilised the mechanical dryers. The leadership and management of the co- operative appeared also to be a factor. These results indicate that both organisational factors and the characteristics of a technology need to be considered in the development and extension of innovation. Overall the results of this work support the individual and organisational adoption literature. Further work could explore this issue on a wider basis across more co-operatives within the region and across more regions in the country. Key words: Technology adoption, co-operatives, mechanical grain dryer.
Keywords: Philippines; Rice; Technological innovations; Drying